INVESTIGATION ON CORROSION AND FLEXURAL BEHAVIOUR OF REINFORCED CONCRETE USING MARINE SAND (Jurnal Teknologi (Sciences & Engineering), 2024)
Traditionally, the construction industry relies on both manufactured sand (known as MF-Sand) and river sand as primary constituents for fine aggregates. However, in response to the dwindling supply of river sand, the contemporary preference is firmly in favor of MF-Sand. This research focuses the utilization of meticulously cleaned marine sand (referred to as MR-Sand) as a superior substitute for MF-Sand, aiming to curtail the reliance on and depletion of river sand, a finite natural resource. The objective of this research is to examine the mechanical property of flexural performance of Reinforced Cement Concrete (RCC) Beam and durability study of concrete using corrosion test in which washed MR - Sand as a fine aggregate in partial replacement of MF-Sand from 20% to 60%. The physical and chemical characteristics of treated and untreated marine sand are compared with a view to better comprehending the features of MR and MF-Sand. Experimental research works have been carried out to look into the corrosion test and flexural strength in order to better understanding the strength and durability attributes of concrete. The values for flexural strength, ultimate load, load-deflection, load-strain, and crack pattern have been compared for the RCC beam specimens MF100, MR20, MR40 and MR60. The findings indicate that 60% of MR-Sand possesses the desired properties of strength and durability of concrete. Additionally, Finite Element Analysis is carried out using the ABAQUS software to further validate the experimental findings of load-deflection, load carrying capacity, crack pattern and flexural strength.